Biomarker derived risk scores predict venous thromboembolism and major bleeding among patients with COVID‐19. Issue 5 (21st July 2022) - Woller, Scott C.; Stevens, Scott M.; Bledsoe, Joseph R.; Fazili, Masarret; Lloyd, James F.; Snow, Greg L.; Horne, Benjamin D.
Abstract: Background: Venous thromboembolism (VTE) risk is increased in patients with COVID‐19 infection. Understanding which patients are likely to develop VTE may inform pharmacologic VTE prophylaxis decision making. The hospital‐associated venous thromboembolism–Intermountain Risk Score (HA‐VTE IMRS) and the hospital‐associated major bleeding–Intermountain Risk Score (HA‐MB IMRS) are risk scores predictive of VTE and bleeding that were derived from only patient age and data found in the complete blood count (CBC) and basic metabolic panel (BMP). Objectives: We assessed the HA‐VTE IMRS and HA‐MB IMRS for predictiveness of 90‐day VTE and major bleeding, respectively, among patients diagnosed with COVID‐19, and further investigated if adding D‐dimer improved these predictions. We also reported 30‐day outcomes. Patients/Methods: We identified 5047 sequential patients with a laboratory confirmed diagnosis of COVID‐19 and a CBC and BMP between 2 days before and 7 days following the diagnosis of COVID‐19 from March 12, 2020, to February 28, 2021. We calculated the HA‐VTE IMRS and the HA‐MB IMRS for all patients. We assessed the added predictiveness of D‐dimer obtained within 48 hours of the COVID test. Results: The HA‐VTE IMRS yielded a c‐statistic of 0.70 for predicting 90‐day VTE and adding D‐dimer improved the c‐statistic to 0.764 with the corollary sensitivity/specificity/positive/negative predictive values of 49.4%/75.7%/6.7%/97.7% and 58.8%/76.2%/10.9%/97.4%, respectively. Among hospitalized and ambulatory patients separately, the HA‐VTE IMRS performed similarly. The HA‐MB IMRS predictiveness for 90‐day major bleeding yielded a c‐statistic of 0.64. Conclusion: The HA‐VTE IMRS and HA‐MB IMRS predict 90‐ and 30‐day VTE and major bleeding among COVID‐19 patients. Adding D‐dimer improved the predictiveness of the HA‐VTE IMRS for VTE.